Digital luxury : transforming brands & consumer experiences - Batat, Wided (SAGE Publications, 2019)
The fashion and luxury industries have been well-established for centuries, but the new disruptive digital environment is causing these industries to rethink their business case and adapt their brand offerings for consumers and experiences both online and offline, mixing physical place and digital space: phygital. This exciting new text, the first on this timely subject, written by an expert author explores the current malaise and offers ways forward through a mixture of research and practice-led examples.- Resumé vydavatel
Keywords: luxusní zboží; internetový marketing; marketing; obchodní značky; luxuries; Internet marketing; brand name products; branding (marketing); elektronické knihy; monografie; electronic books; monographs